Use peripheral blood leukocyte parameters combined with inflammatory indicators in diagnosis and severity assessment of mycoplasma pneumoniae pneumonia in children - Yuwen Zhang; Yuanpeng Zhai; Shuai Qi; Dan Huang; Jingjing Wang; Linyan Wang; Xuemei Dong; Zhipeng Sun; Jiaojiao Yin; Chong Zhang; Weikai Wang (PLoS ONE, 2025)
Background Mycoplasma pneumoniae is a common cause of pneumonia in children over 5 years of age. Cell Population Data (CPD) is valuable for screening various diseases, including certain infections and myeloproliferative disorders, but less used in the diagnosis of children mycoplasma pneumoniae pneumonia (MPP). Aims To improve the diagnostic efficacy and severity assessment of MPP in children by combining CPD with inflammatory markers. Methods This study was conducted at the Gansu Provincial Maternity and Child-care Hospital, China. The data was accessed on 01.10.2024 for the purpose of research. A retrospective study from 01.10. 2022–01.01.2024 included three groups of children aged 5–9 years: 1) those with MPP (n = 240), of which 73 were mild, 167 were severe; 2) those with bacterial pneumonia (n = 52); and 3) those with health check-ups (n = 340). CPD indicators were measured by Sysmex XN-9000 (Kobe, Japan) hematology analyzer. Inflammatory markers included PCT (procalcitonin), LDH (lactate dehydrogenase), CK-MB (creatine kinase isoenzyme), CRP (c-reactive protein), SAA (serum amyloid A), APTT (activated partial thromboplastin time), FIB (fibrinogen). The differences and correlation of parameters between three groups were analyzed and receiver operating characteristic (ROC) analysis was performed. Results Most of the leukocyte parameter indices showed statistically significant differences between the MPP group and the healthy physical examination group (p < 0.05). Compared with bacterial pneumonia group, inflammatory markers were not correlated with the occurrence of MPP (p > 0.05), while LY-X and NE-WY were negatively correlated with the occurrence of MPP (p < 0.05). ROC analysis showed that the areas under the curve (AUC) for LY-X and NE-WY were 0.707 and 0.736, respectively. Additionally, LY-WY and MO-WZ are positively correlated with the severity of MPP (p < 0.05), and the AUC for MO-WZ was 0.709. Among the inflammatory markers, the AUC for SAA was 0.828, and combining SAA with MO-WZ increased the AUC to 0.861 in distinguishing mild from severe MPP. Conclusion Peripheral blood leukocyte parameters may have clinical application value for the early diagnosis and disease progression assessment of MPP.